Anatomical study of C2 pedicle and pars interarticularis in thai population - Akkapong Nitising (2018)
© 2017, Medical Association of Thailand. All rights reserved. Background: The C2 pedicle and pars interarticularis complex have distinct anatomy and substantial variation in the population. The exact locations of the C2 pedicle and pars interarticularis are still controversial. Objective: This study aims to determine the safe trajectory and length of C2 pedicle and pars screw insertion. Material and Method: Thirty-six dried cadaveric C2 vertebrae were used in this study. The authors measured four linear and four angular parameters of C2 pedicle and pars interarticularis by using a Vernier caliper and a digital goniometer. Results: Regarding C2 pedicle screw placement, the entry point is a point 5 mm inferior to the superior border of the C2 lamina and 7 mm lateral to the lateral border of the spinal canal, the axial angle is 30°, the sagittal angle is 28° and the length of the distance is 27 mm. For C2 pars screw insertion, the appropriate entry point is a point 3 to 4 mm superior and lateral to the medial aspect of the C2-3 facet joint, the axial angle is 16°, the sagittal angle is 36° and the length of the distance is 30 mm. Conclusion: The authors proposed recommendation for safe C2 pedicle and pars screw placement. These landmarks are suitable for Thai population.